Leadership Principal In improving teacher's ability to implement Independent Curriculum at State Elementary School 134 Palembang - Mustika Sari Mahfirah; Meilia Rosani; Mahasir Mahasir (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to provide a detailed and in-depth description of school leadership, obstacles, and solutions in improving teachers' abilities to implement the Merdeka Curriculum at SD 134 Palembang. The research was conducted from December to February 2025 at SD 134 Palembang, involving 48 teachers and 7 educational staff as samples. The study employed a qualitative descriptive research approach, utilizing data collection techniques through interviews, field observations, and triangulation.The principal of SD 134 Palembang has fostered a positive school environment, evident in their active role in enhancing teachers' competencies in implementing the Merdeka Curriculum. The Merdeka Curriculum grants schools and teachers greater autonomy in designing learning that aligns with students' needs and potential. This necessitates teachers possessing adequate capabilities to effectively implement the Merdeka Curriculum. This study aimed to improve teachers' abilities at SD 134 Palembang in implementing the Merdeka Curriculum through training and mentoring.The study employed a qualitative method with a classroom action research design. The research subjects were the teachers at SD 134 Palembang. Data were collected through observation, interviews, and documentation. Data were analyzed using qualitative data analysis techniques.The findings revealed that training and mentoring were effective in enhancing teachers' capabilities in implementing the Merdeka Curriculum.